Faktor-Faktor yang Mempengaruhi Kenaikan Harga Saham IPO di Bursa Efek Indonesia Periode Tahun 2021 - MARSELIA PURNAMA; Octavianti Purnama; Ari Nuratriningrum (Primanomics : Jurnal Ekonomi & Bisnis, 2023)
This study focuses on the prices of newly listed stocks on the Indonesian Stock Exchange during 2021 and was conducted on the Indonesian Stock Exchange. purposive sampling method used in this study as sampling method. Stocks listed on the Indonesian Stock Exchange in 2021 are used as the sample, so 53 observations are obtained. In this study, hypothesis testing was done in five ways: multiple linear regression analysis, classical hypothesis test, simultaneous test (f test), partial test (t test) and coefficient of determination test. In this study, only the underwriter variable was found to have a significant effect on the IPO stock price increase in the Indonesian Stock Exchange, with a significance level of 0.0032. Other variables, i.e. public ownership percentage, number of outstanding shares, EPS and listing board category do not significantly affect IPO share price increase in the Indonesian Stock Exchange.